High trend inflation and passive monetary detours - Guido Ascari; Anna Florio; Alessandro Gobbi (Bank of Finland, 2018)
According to the long-run Taylor principle (Davig and Leeper, 2007), a central bank can deviate to a passive monetary policy and still obtain equilibrium uniqueness if a sufficiently aggressive monetary policy is expected for the future. Does this principle hold true when both monetary and fiscal policies can switch between active and passive and there is positive trend inflation? We find that passive monetary detours are no longer possible when trend inflation is high, whatever fiscal policy is in place. This has important policy implications in terms of flexibility and monetary-fiscal authorities coordination.
URN:NBN:fi:bof-201802261245
Keywords: E52; E62; 330